Neuro-immune interactions in chemical-induced airway hyperreactivity. Issue 2 (28th April 2016) - Devos, Fien C.; Boonen, Brett; Alpizar, Yeranddy A.; Maes, Tania; Hox, Valérie; Seys, Sven; Pollaris, Lore; Liston, Adrian; Nemery, Benoit; Talavera, Karel; Hoet, Peter H.M.; Vanoirbeek, Jeroen A.J.
Asthma may be induced by chemical sensitisers, via mechanisms that are still poorly understood. This type of asthma is characterised by airway hyperreactivity (AHR) and little airway inflammation. Since potent chemical sensitisers, such as toluene-2, 4-diisocyanate (TDI), are also sensory irritants, it is suggested that chemical-induced asthma relies on neuro-immune mechanisms. We investigated the involvement of transient receptor potential channels (TRP) A1 and V1, major chemosensors in the airways, and mast cells, known for their ability to communicate with sensory nerves, in chemical-induced AHR. In vitro intracellular calcium imaging and patch-clamp recordings in TRPA1- and TRPV1-expressing Chinese hamster ovarian cells showed that TDI activates murine TRPA1, but not TRPV1. Using an in vivo model, in which an airway challenge with TDI induces AHR in TDI-sensitised C57Bl/6 mice, we demonstrated that AHR does not develop, despite successful sensitisation, in Trpa1 and Trpv1 knockout mice, and wild-type mice pretreated with a TRPA1 blocker or a substance P receptor antagonist. TDI-induced AHR was also abolished in mast cell deficient Kit Wsh / Wsh mice, and in wild-type mice pretreated with the mast cell stabiliser ketotifen, without changes in immunological parameters. These data demonstrate that TRPA1, TRPV1 and mast cells play an indispensable role in the development of TDI-elicited AHR. Chemical-induced AHR relies on neuro-immune interactions, involving lymphocytes, TRP channels and mast cells http://ow.ly/Z4LtH